Wirausaha Kelompok Usaha Budidaya Pembesaran Lele - Bambang Sugeng Dwiyanto; Jemadi Jemadi (Universitas Proklamasi 45 Yogyakarta, 2014)
Business Group Catfish Aquaculture enlargement as a form of response to the community groups who are in RT 01 and RT 02 Somoitan, Girikerta, Turi, Sleman, who wish to pioneer the cultivation of catfish, but they are faced with: 1). Production problems in the form of limited/partners of the limited knowledge: a). On preparation techniques for the cultivation of fish rearing pondcat fish. b). stocking of cat fish. c).enlargement process includes feeding catfish, prebiotics and vitamins, water treatment pond and high settings. d). about the harvest which includes sorting the harvest and transport fish. 2). Management problems that include both partners still lack knowledge about: a). How to access capital financial institution Bank/Non-Bank. b). Including financial management analyst investment costsand production costs as well as production breakeven analysis (Break Even Point/BEP) efforten large ment cat fish. c). About entrepreneurship, especially in business planning. The method used to overcome the problem of training and practice are partners as well as mentoring. The training consiste do ftraining and practice etraining the fish pond preparation, seeding, maintenance catfish, fish harvesting, training how to access capital, financial management training business, and entrepreneurship training and business planning. The results of this activityis the increase of knowledge, under standing and skills of the participants in the cultivation of catfish rearing which includes the ability to preparea fishpond, stocking, maintenance and harvesting. In terms of partner management business grouph as been an increase in knowledge, understanding and skills of participants in the field of access to capital, management of business financial management, entrepreneurship and business planning. While mentoring partners can be expected to start catfish farming sustainable enlargement to improvethe economic welfare ofthe group members.